A Sensitive and Rapid Method for Detecting Formaldehyde in Brain Tissues. (24th September 2017) - Yue, Xiangpei; Zhang, Yaoyue; Xing, Wen; Chen, Yutong; Mu, Chenyang; Miao, Zhan; Ge, Peichun; Li, Tingting; He, Rongqiao; Tong, Zhiqian
Abstract : The existing methods for detecting formaldehyde (FA) in brain samples are expensive and require sophisticated experimental procedures. Here, we established a highly sensitive and selective spectrophotometric method, which is based on a reaction in which FA reacts with colorless reagent 4-amino-3-penten-2-one (Fluoral-P) to produce a yellow compound, 3, 5-diacetyl-1, 4-dihydrolutidine (DDL), which can be detected by a spectrophotometer at 420 nm at room temperature. The sensitive response time point was found to be at the first hour, and the optimal pH of derivative reaction was pH 6.0. The limit of detection (LOD) and the limits of quantization (LOQ) for detecting FA were 0.5 μ M and 2.5 μ M, respectively. Using this method, an abnormally high level of FA was detected in both the brains of FA-injected mice and autopsy hippocampus tissues from patients with Alzheimer's disease. This finding suggests that the modified Fluoral-P method is effective for measuring levels of FA in the brains.